FORMULATION, STANDARDIZATION, AND EVALUATION OF POLYHERBAL DISPERSIBLE TABLET - Maurya, Harikesh; Kumar, Tirath (International Journal of Applied Pharmaceutics, 2019)
Objective: The study was designed as formulation, standardization, and evaluation of polyherbal dispersible tablet prepared for the management of kidney disorders. To overcome the problem of dyspepsia in geriatric patients by the use of polyherbal dispersible tablets. Methods: Dispersible tablets were prepared using aqueous root extract powder of the selected plant viz.Â A.Â officinalis,Â B.Â diffusa,Â C. papaya,Â C. fistula, C.Â intybus, F.Â hispida, F. indica,Â C.Â nurvala,Â S.Â virgaurea,Â andÂ V.Â negundoÂ with the help of superdisintegrant addition technique usingÂ crospovidone, sodium starch glycolate andÂ croscarmelloseÂ sodium in different percentage. Evaluation assessments such as the substantial test, weight variation, hardness, friability, content uniformity, disintegration,Â in vitroÂ dispersion, stability study and IR compatibility were carried out. Results: Micromeritics of extracts powder were determined for all formulation, which signifying good flow properties. The substantial examination was established, which comply with official requirements for uniformity test, and the drug content was close to 100% in all formulations. Disintegration time was observed for all formulation in which the polyherbal formulation-3 (PHF-3) showing 1.10Â±0.10 min; duringÂ in vitroÂ dispersion time, all formulation showed appropriate dispersion in which the PHF-3 captivating 2.00Â±0.45 min only. The IR compatibility shows none chemical interaction between the extracts and excipients. Conclusion: The PHF-3 showed satisfactory disintegration andÂ in vitroÂ dispersion time due to crospovidone and reported as the best formulation. The stability study and IR compatibility validate the PHF may represent new easily swallow dispersible tablet that may enhance drug permeability and advance bioavailability for nephrotic patients. Â